Needs of Indonesian Short Story Writing Material: A Case Study of Foreign Students at ACS School Jakarta - Tri Maryanto; Endry Boeriswati; Liliana Muliastuti (Indonesian Language Education and Literature, 2018)
The purposes of study into identify the needs of Indonesian short story writing material for foreign students at ACS Jakarta school. The method used qualitative research. The process of collecting data used observation activities, interviews, and questionnaire. Validation of data is triangulation process. The results showed that the foreign students need materials have a variation level in accordance with the context of learning which is Indonesian. Students expect Indonesian language short story writing material that is relevant to their language cultural context and culture in the Indonesian language. While the teaching materials is supported by the use of learning media is able to stimulate the learning activities of writing.Penelitian ini bertujuan untuk mengidentifikasi kebutuhan bahan ajar menulis cerita pendek bahasa Indonesia bagi siswa penutur asing di sekolah ACS Jakarta. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif. Proses pengumpulan data menggunakan kegiatan observasi, wawancara, dan kuesioner. Validasi data menggunakan proses triangulasi. Hasil penelitian menunjukkan bahwa siswa penutur asing membutuhkan bahan ajar yang memiliki tingkat variasi sesuai dengan konteks pembelajaran bahasa Indonesia. Para siswa mengharapkan adanya sajian materi ajar menulis cerita pendek yang relevan dengan konteks dan budaya dalam bahasa Indonesia. Selain itu, materi ajar didukung oleh penggunaan media belajar yang mampu menstimulasi kegiatan pembelajaran menulis.